2016
DOI: 10.1002/slct.201600009
|View full text |Cite
|
Sign up to set email alerts
|

Gold‐NHC complexes as potent bioactive compounds

Abstract: This report describes the evaluation of the biological activities of 13 gold‐NHC complexes. These complexes were evaluated in vitro for their antioxidant properties, α‐glucosidase, thymidine phosphorylase, β‐glucuronidase and xanthine oxidase enzyme inhibition activities. Among the tested complexes, those bearing chloride ligands were found to be potent antioxidant, α‐glucosidase, thymidine phosphorylase, β‐glucuronidase and xanthine oxidase enzyme inhibitors, showing several hundred fold higher activity than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 81 publications
0
30
0
Order By: Relevance
“…Most of the biomedical studies on silver–NHC complexes have been conducted with regard to their antimicrobial properties . Although the cytotoxic effects of silver compounds against bacteria have long been established, the mechanisms of action are not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the biomedical studies on silver–NHC complexes have been conducted with regard to their antimicrobial properties . Although the cytotoxic effects of silver compounds against bacteria have long been established, the mechanisms of action are not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Thus metal-NHC compounds show promise for catalytic applications 14 and also in the biological field. 15,16 For similar reasons, NHCs have attracted much attention in the development of novel nanoparticles [17][18][19][20][21][22][23][24][25][26] as it is estimated that the Au-NHC bond strength is about double that of a corresponding Au-thiol bond, 27 and recent reports show that NHC functionalized AuNPs and gold surfaces outperformed their thiol based counterparts with regards to thermal and chemical stability. 24,27,28 Amongst AuNPs, those with chiral ligands are of particular interest due to their potential applications in optics, asymmetric catalysis and chiral discrimination.…”
mentioning
confidence: 99%
“…In 2016, Al‐Majid et al reported the biological activities of 13 gold‐NHC complexes. Two complexes, [IPrH][Au(Cl) 2 (130) and [IPrH][Au(Cl) 4 (131) , were found to have antioxidant and XO inhibition properties due to ionic nature . Cao et al.…”
Section: Xanthine Oxidasementioning
confidence: 99%